Investigating the reactivity of TiOx and BDD anodes for electro-oxidation of organic pollutants by experimental and modeling approaches. (20th January 2023) - Ma, Jing; Trellu, Clément; Skolotneva, Ekaterina; Oturan, Nihal; Oturan, Mehmet A.; Mareev, Semyon
Highlights: Model took into consideration mass transport, ⋅ O H -mediated oxidation and DET. Reactivity of BDD and TiOx for degradation and mineralization was compared. The role of each phenomenon was discussed in different experimental configurations. The predominant mechanism depends on ⋅ O H scavengers and reaction rates. 100 mM ethanol was necessary for relevant ⋅ O H quenching experiment. Abstract: The reactivity of two non-active anodes (BDD and TiOx ) for the removal of organic pollutants from water was investigated and compared. A mathematical model for electro-oxidation of organic compounds was developed by considering (i) an analytical expression of the spatial distribution of OH concentration at non-active anodes, (ii) mass transport through the diffusion boundary layer and (iii) both direct electron transfer and OH-mediated oxidation for degradation of organic pollutants. The model was calibrated from experimental data using, for example, terephthalic acid as OH probe molecule or ethanol as OH quencher during paracetamol degradation. Calculation of the fraction of current ascribed to the different possible reactions as well as a sensitivity analysis allowed for highlighting the key mechanisms and limiting phenomena. Degradation of organics occurs almost exclusively through OH-mediated oxidation under mass transport limitation and for sufficiently high reaction rate constants. Improvement of degradation kinetics strongly depends on mass transport enhancement of organic compounds to the reaction zone at the electrode surface. Competition between the mother molecule and degradation by-products for reaction with OH did not significantly affect degradation kinetics under mass transport limitation. Direct electron transfer can potentially become important in presence of large amounts of OH scavengers or for organic compounds that react slowly with OH (k < 10 5  m 3 mol −1 s −1 ). Results also showed that the implementation of a suitable OH quenching experiment required the use of a concentration of ethanol of at least 100 mM for experiments performed at 5 mA cm −2 and with a concentration of target pollutant of 0.1 mM. Graphical abstract: Image, graphical abstract